2020
DOI: 10.17072/2079-7877-2020-2-130-140
|View full text |Cite
|
Sign up to set email alerts
|

Microelement Composition of the Snow Cover in the Berezniki Urban District (Perm Region)

Abstract: Urbanized areas experience heavy technological load, especially if the core of the city is associated with industrial activities. In 2018, the Perm region ranked fourth in the Volga Federal District in terms of air emissions. Chemical and mining activities in the Berezniki urban district of the Perm region make a huge contribution to increasing air pollution. Previously, it was established that the distribution of pollutants across the city was affected by the physical and geographical characteristics of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…- [Khayrulina and Ushakova, 2020]. On the basis of the microelement assessment in Berezniki, it was found that recreational areas (recreational zone) are exposed to an increased technogenic impact relative to the industrial ones, where the total pollution index Zc was 33.6 and 30.1, respectively [Ushakova et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…- [Khayrulina and Ushakova, 2020]. On the basis of the microelement assessment in Berezniki, it was found that recreational areas (recreational zone) are exposed to an increased technogenic impact relative to the industrial ones, where the total pollution index Zc was 33.6 and 30.1, respectively [Ushakova et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Ushakova et al, 2020]. High anthropogenic impact is characteristic of the recreational zones of many industrial centers.…”
mentioning
confidence: 99%